2021
DOI: 10.1080/23311975.2021.1908004
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal loan growth and bank risk-taking in Vietnam: A quantile regression approach

Abstract: We empirically investigate and present evidence of nonlinearity and heterogeneity in the impact of abnormal loan growth on risk-taking in the Vietnamese banking system between 2007 and 2019, using a quantile regression method. Our results showed that abnormal loan growth initially helped banks to reduce risk-taking. However, this relationship was U-shaped and heterogeneous. The effect of abnormal loan growth was more significant for banks at the upper tail of the risk-taking distribution. Our findings also dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Note that ZSCORE is an inverse measure of overall banking risk. This variable is widely used in the literature such as Le (2021), Le et al (2020), Le et al (2019) and Ho et al (2021). SHIFTi,t , the household credit to firm credit ratio in the banking system of the country i in year t is calculated based on the data provided by Léon (2018) is used to control for the shift in lending activities toward households.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that ZSCORE is an inverse measure of overall banking risk. This variable is widely used in the literature such as Le (2021), Le et al (2020), Le et al (2019) and Ho et al (2021). SHIFTi,t , the household credit to firm credit ratio in the banking system of the country i in year t is calculated based on the data provided by Léon (2018) is used to control for the shift in lending activities toward households.…”
Section: Methodsmentioning
confidence: 99%
“…1. Prior studies on this aspect show mixed findings. Several studies found a positive association between loan growth and bank stability (Sinkey and Greenawalt, 1991; Laeven and Majnoni, 2003; Ho et al , 2021). However, others show opposite results (Le, 2018, 2020).…”
Section: Notesmentioning
confidence: 99%